Prognostic relevance of miR-124-3p and its target TP53INP1 in pediatric ependymoma - Margolin‐Miller, Yulia; Tzaridis, Theophilos-Dimitrios; Pfister, Stefan; Witt, Hendrik (Genes, chromosomes & cancer, 2017)
Ependymoma is a malignant pediatric brain tumor, often incurable under the current treatment regimen. We aimed to evaluate the expression of microRNAs (miRs) in pediatric ependymoma tumors in an attempt to identify prognostic molecular markers which would lead to potential therapeutic targets. Following miR-array expression analysis, we focused on 9 miRs that correlated with relapse which were further validated by quantitative real-time PCR (qRT-PCR) in a cohort of 67 patients. Western blotting and immunohistochemistry were used to measure target protein expression in 20 and 34 tumor samples, respectively. High expression of miR-124-3p significantly correlated with the lower progression-free survival (PFS) of 16% compared to 67% in those expressing low levels (P = .002). Interestingly, in the group of patients with local disease (n = 56) expression levels of this miR distinguished 2 subgroups with a significantly different outcome (P = .001). miR-124-3p was identified as an independent prognostic factor of relapse in the multivariate analysis performed in the whole cohort and in the group with localized disease. In the localized group, a patient expressing high levels of miR-124-3p had a 4.1-fold increased risk for relapse (P = .005). We demonstrated the direct binding of miR-124-3p to its target TP53INP1. Negative TP53INP1 protein levels correlated with a poor outcome (P = .034). We propose miR-124-3p and TP53INP1 as new biomarkers for prognostic stratification that may be possible therapeutic targets for ependymoma.
Gesehen am 02.10.2018